2022
DOI: 10.1111/sltb.12847
|View full text |Cite
|
Sign up to set email alerts
|

The Screen for Nonsuicidal Self‐Injury: Development and initial validation among veterans with psychiatric disorders

Abstract: Introduction Nonsuicidal self‐injury (NSSI) is associated with significant impairment and is a robust predictor of suicidal ideation, attempts, and death by suicide; however, the present lack of a brief screening instrument for NSSI coupled with consistent underidentification of NSSI in male adults has led to concerning rates of missed identification of NSSI. Methods The Screen for Nonsuicidal Self‐Injury (SNSI) is a brief, 10‐item screen designed to identify individuals currently engaging in NSSI with an emph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 62 publications
2
3
0
Order By: Relevance
“…Consistent with Mann et al's (2022) suggestion that it may be more likely for NSSI by proxy to follow traditional NSSI in time, findings across both studies revealed a significantly earlier age of onset for traditional NSSI versus NSSI by proxy. One explanation may be that individuals transition from NSSI to NSSI by proxy due to the stigma associated with traditional NSSI behaviors and the greater ability to hide the self-injurious intentions of their behaviors in the context of NSSI by proxy.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Consistent with Mann et al's (2022) suggestion that it may be more likely for NSSI by proxy to follow traditional NSSI in time, findings across both studies revealed a significantly earlier age of onset for traditional NSSI versus NSSI by proxy. One explanation may be that individuals transition from NSSI to NSSI by proxy due to the stigma associated with traditional NSSI behaviors and the greater ability to hide the self-injurious intentions of their behaviors in the context of NSSI by proxy.…”
Section: Discussionsupporting
confidence: 70%
“…The top four reasons for preferring traditional NSSI to NSSI by proxy were consistent across samples and focused on the perception of traditional NSSI as more in the respondent's control, easier to do, easier to hide, and more immediate. Conversely, for the small subset of participants who reported preferring NSSI by proxy, one of the most commonly endorsed reasons for this preference across both studies was the perception of NSSI by proxy as more socially acceptable, consistent with Mann et al's (2022) proposal that NSSI by proxy may be preferred by some individuals because it is viewed as more socially acceptable than traditional NSSI. As noted above, it is possible that the perception of NSSI by proxy as more socially acceptable could, for some individuals, lead to a transition from traditional NSSI to NSSI by proxy over time (within or outside the context of therapy).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Indeed, although tattooing and body piercing are most frequently performed by an “other” (Bone et al, 2008), past NSSI research has examined these behaviors as NSSI when they are performed by the individual themselves (see Lloyd‐Richardson et al, 2007). For example, the Self‐Injurious Thoughts and Behaviors Interview (SITBI; Nock et al, 2007) and the Functional Assessment of Self‐Mutiliation (FASM; Lloyd et al, 1997) include tattooing oneself as a form of NSSI, the Screen for Nonsuicidal Self‐Injury (Halverson et al, 2022) includes the self‐insertion of needles into one's body as a form of NSSI (without excluding body piercing), and the Alexian Brothers Assessment of Self‐Injury (Washburn et al, 2015) includes both tattooing and piercing oneself as forms of NSSI. Thus, given that the only difference between self‐tattooing/self‐piercing and conventional tattooing/body piercing by a professional/“other” is the involvement of another person as the inflictor of the bodily tissue damage, considering tattooing and piercing by an “other” as a potential form of NSSI by proxy is consistent with extant operational definitions of NSSI that consider self‐tattooing/self‐piercing as a form of NSSI.…”
Section: Nssi By Proxy Behaviorsmentioning
confidence: 99%
“…Further, our results indicated that lactational mastitis was associated with an increased risk of self-harm or suicidal ideation. Recent studies suggested that self-harm is a strong predictor of suicide attempts and a more powerful predictor than other suicide risk factors ( 29 ). Therefore, our findings provide evidence that lactational mastitis increases the risk of depression and self-harm or suicidal ideation during the postpartum period.…”
Section: Discussionmentioning
confidence: 99%